Mario Botta Architecture 1960-2010 - Pisani, Mario (I+Diseño. Revista Científica de Investigación y Desarrollo en Diseño, 2010)
Why is Botta's work so important? Because he understood before others that the time had come "to take a new path within the complexity of post-industrial society". In the words of Carlo Bertelli, his architecture is characterised by the poetics of listening, of places and people. An inexhaustible willingness to listen to the territory and those who inhabit it. A listening that goes beyond the self-referential fact —the house or the church à la Botta— to take in and make its own the stimuli, the suggestions, the paths that seek to give substance and concreteness to the design intuition.